2013
DOI: 10.1111/josh.12114
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use and Sexual Risk Behaviors Among American Indian and Alaska Native High School Students

Abstract: BACKGROUND We describe the prevalence of behaviors that put American Indian and Alaska Native (AI/AN) high school students at risk for teen pregnancy and sexually transmitted infections (STIs) and the relationships among race/ethnicity and these behaviors. METHODS We analyzed merged 2007 and 2009 data from the national Youth Risk Behavior Survey, a biennial, self-administered, school-based survey of US students in grades 9–12 (N =27,912). Prevalence estimates and logistic regression, controlling for sex and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 16 publications
1
58
0
Order By: Relevance
“…AI/AN adolescents have the highest substance use and related morbidity and mortality of any US group (Baldwin, Maxwell, Fenaughty, Trotter, & Stevens, 2000;Beauvais, 1992;Blum, Harmon, Harris, Bergeisen, & Resnick, 1992;Substance Abuse and Mental Health Services Administration, 2004;Walters, Simoni, & Harris, 2000). They are more likely to initiate drug and alcohol use before the age of 13 and on average have higher rates of lifetime drug use than other adolescent groups (de Ravello, Everett Jones, Tulloch, Taylor, & Doshi, 2014). Substance use risk is compounded by risky sexual behavior and poor sexual health among AI/AN adolescents.…”
Section: Please Scroll Down For Articlementioning
confidence: 98%
“…AI/AN adolescents have the highest substance use and related morbidity and mortality of any US group (Baldwin, Maxwell, Fenaughty, Trotter, & Stevens, 2000;Beauvais, 1992;Blum, Harmon, Harris, Bergeisen, & Resnick, 1992;Substance Abuse and Mental Health Services Administration, 2004;Walters, Simoni, & Harris, 2000). They are more likely to initiate drug and alcohol use before the age of 13 and on average have higher rates of lifetime drug use than other adolescent groups (de Ravello, Everett Jones, Tulloch, Taylor, & Doshi, 2014). Substance use risk is compounded by risky sexual behavior and poor sexual health among AI/AN adolescents.…”
Section: Please Scroll Down For Articlementioning
confidence: 98%
“…14 In addition, AI/AN youth likely have higher rates of teen pregnancy because of social and economic disparities, such as poverty, 15,16 drug and alcohol use, 17-20 and physical/sexual abuse. 16,21-23 Evidence also suggests that AI/AN youth initiate sex at earlier ages when compared to other ethnic groups. 13 For example, one study of AI youth in Minnesota found that almost 70% of 16-to-18 year-olds and 42% aged 13 to 15 reported they had ever had sexual intercourse, 24 compared to a national US study that found 32% of 15-to-17 year-olds had ever had sex.…”
mentioning
confidence: 99%
“…This result is consistent with the study conducted in preparatory schools youth in Addis Ababa (Dereje et al, 2015). Study in U.S.A (de Ravello et al, 2014) also showed that early sexual intercourse before age 13 year increases the likelihood of involvement in other risky sexual behavior. In this study, significant proportion of school youth had their fist sexual intercourse before age 15 years and the longer time of sexual experience was followed by change of partner and others risky behavior.…”
Section: Discussionmentioning
confidence: 99%